External validation of a novel risk model in patients with favorable risk renal cell carcinoma defined by international metastatic renal cell carcinoma database consortium (imdc): results from the turkish oncology group kidney cancer consortium (tkcc) database - ARIKAN, RUKİYE (My University, 2022)
© 2022Background: A novel prognostic model was recommended for patients with metastatic RCC (mRCC) by the International mRCC Database Consortium (IMDC). In this study, we aimed to externally validate a novel risk model for the IMDC-favorable risk group in patients with mRCC. Methods: The Turkish Oncology Group Kidney Cancer Consortium (TKCC) is a multicenter registry that includes 13 cancer centers in Turkey. As described by Schmidt et al., 3 parameters (ie, time from diagnosis to systemic therapy 80, and the presence of brain, liver, or bone metastasis) were used to divide the IMDC favorable risk group into 2 new categories: very favorable and favorable risk groups. The primary endpoint was overall survival (OS). Time to treatment failure (TTF) and objective response rate (ORR) in the very favorable and favorable risk groups were the secondary endpoints. Results: A total of 545 patients with mRCC from all IMDC risk groups and 112 patients from the favorable risk group were included in this study. According to the novel classification model, 44 (39.3%) and 68 (60.7%) patients with former favorable risk were categorized into very favorable and favorable risk groups, respectively. The median OS (55.8 months vs. 34.2 months, P =.025) and TTF (25.5 months vs. 15.5 months, P =.010) were longer in the very favorable risk group than in the favorable risk group. The concordance index of the new IMDC model in all patients was 0.65 for OS. Despite the higher ORR in the very favorable risk group than in the favorable risk group, the difference between the groups was not statistically significant (52.4% vs. 44.7, P =.573). Conclusions: This was the first study to externally validate the novel IMDC risk model presented in the American Society of Clinical Oncology Genitourinary Cancers Symposium 2021.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Nefroloji; Onkoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Nephrology; Oncology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ÜROLOJİ VE NEFROLOJİ; ONKOLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; UROLOGY & NEPHROLOGY; ONCOLOGY; Üroloji; Urology; Renal Cell Carcinoma; Risk groups; Very favorable